2017
DOI: 10.1002/gj.2893
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐proxy approach to palaeoenvironmental modelling: the English Lower Cretaceous Weald Basin

Abstract: Palaeoenvironmental reconstructions of the Wealden (Lower Cretaceous) in southeast England have been previously based mainly on field and fossil data. This study presents new interpretations of multi-proxy data sets such as sandstone petrography, elemental geochemistry and sideritic ironstones, supplemented by outcrop and clay mineralogical data. The dominance of quartz arenites, kaolinite and thorium and the presence of Zr in the sediments suggest that they were sourced mainly from granitic and/or gneissic ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 137 publications
(316 reference statements)
3
15
0
Order By: Relevance
“…Some sandstones display a combination of tight and loose cementation. Geochemical analysis confirmed that the iron stains observed in the thin sections are siderites (Akinlotan, , ,b). In the base of the Wadhurst Clay Formation (syntaxial) quartz overgrowth forms a secondary outline on the primary quartz grain.…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…Some sandstones display a combination of tight and loose cementation. Geochemical analysis confirmed that the iron stains observed in the thin sections are siderites (Akinlotan, , ,b). In the base of the Wadhurst Clay Formation (syntaxial) quartz overgrowth forms a secondary outline on the primary quartz grain.…”
Section: Resultssupporting
confidence: 53%
“…In any case, the role of climate on clay mineral composition is well‐documented in the Weald and beyond (Singer, , ; Sladen, ; Sladen & Batten, ; Moore & Reynolds, ; Hallam et al ., ; Oboh, ). For instance, spectral gamma‐ray data on the Wealden deposits in the Weald (Akinlotan, , 2017b) correlate well with palaeoclimate interpretations made from the data presented in this study. Thorium is normally enriched when kaolinite is formed from the alteration of feldspars (Ruffell & Worden, ; Schnyder et al ., ) and its significant quantity in the Wealden rocks point to the dominantly warm with periodically wet conditions that favoured the intensive weathering that is required for the formation of kaolinite.…”
Section: Interpretation and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ph.D. thesis, Univ. Brighton, 2015; Akinlotan, 2017 c ). The Ashdown, Wadhurst Clay and Tunbridge Wells Sand formations informally referred to as the Hastings Beds (Berriasian–Valanginian) make up the lower section of the Weald Basin.…”
Section: Geological Settingmentioning
confidence: 99%
“…Ph.D. thesis, Univ. Brighton, 2015; Akinlotan, 2017 c ). The rocks within this formation were deposited in predominantly fluvial and non-marine environments under both braided and meandering river systems.…”
Section: Geological Settingmentioning
confidence: 99%